A Survey of Vehicle System and Energy Models - Lingyun Hua; Jian Tang; Guoming Zhu (Actuators)
Vehicle system models can be roughly divided into two categories, dynamic and steady-state (or quasi-steady-state) models, and can be applied to evaluate vehicle transient performance such as vehicle longitudinal and lateral dynamics, as well as energy economies like fuel or electricity consumption. This paper reviews various energy consumption models for automotive systems, focusing on component- and vehicle-level models. As the foundation to calculate the energy consumption, powertrain component models of three main vehicle types (internal combustion engine (ICE) vehicles, electric vehicles (EVs), and hybrid vehicles) are reviewed with their key components, including internal combustion engines, electric motors, and batteries. Three types of vehicle energy consumption models are explored according to their interpretability: white-box, black-box, and grey-box models. Optimizing vehicle energy usage based upon a vehicle energy consumption model is reviewed from the aspects of eco-driving and eco-routing problems at the end of the paper. Eco-driving research primarily selects models focusing on transient performance; whereas eco-routing focuses on steady-state or quasi-steady-state conditions to balance the needs of model accuracy and calculation efficiency for real-time applications. This review aims to guide model selection and inspire future applications of energy consumption models for advancing sustainable automotive technologies.